The rôle of human resources training in the quality of marketing within the sports facility - benarous.mohamed,; hadab salim, (sports creativity, 2025)
Most of the developments in the field of modern human resources management especially in the field of quality of marketing services within sports facilities accompanied by a number of transformations have forced each sports facility to search on the best ways to develop its management system to increase the performance of its human resources through the training function which is considered Dimensional strategies of human resources and money of importance within the organizational structure the outcome in the subject of marketing for some sports facilities is reflected by the progress in the use of modernsports management of contemporary methods in all its activities through training and training for all employees.